Traditional uses, phytochemistry, pharmacology, quality control and clinical studies of Cimicifugae Rhizoma: a comprehensive review - Qianqian Zhang; Wei Wei; Xingyue Jin; Jin Lu; Shujing Chen; Omachi Daniel Ogaji; Shaoxia Wang; Kunze Du; Yanxu Chang; Jin Li (BMC, 2024)
Abstract Cimicifugae Rhizoma, generally known as "Sheng Ma" in China, has great medicinal and dietary values. Cimicifugae Rhizoma is the dried rhizome of Cimicifuga foetida L., Cimicifuga dahurica (Turcz.) Maxim. and Cimicifuga heracleifolia Kom., which has been used to treat wind-heat headache, tooth pain, aphtha, sore throat, prolapse of anus and uterine prolapse in traditional Chinese medicine. This review systematically presents the traditional uses, phytochemistry, pharmacology, clinical studies, quality control and toxicity of Cimicifugae Rhizoma in order to propose scientific evidence for its rational utilization and product development. Herein, 348 compounds isolated or identified from the herb are summarized in this review, mainly including triterpenoid saponins, phenylpropanoids, chromones, alkaloids, terpenoids and flavonoids. The crude extracts and its constituents had various pharmacological properties such as anti-inflammatory, antitumor, antiviral, antioxidant, neuroprotective, anti-osteoporosis and relieving menopausal symptoms. The recent research progress of Cimicifugae Rhizoma in ethnopharmacology, phytochemistry and pharmacological effects demonstrates the effectiveness of its utilization and supplies valuable guidance for further research. This review will provide a basis for the future development and utilization of Cimicifugae Rhizoma.